Population parameters and bio-exploitation status of Indian Mackerel (Rastrelliger kanagurta Cuvier, 1816) in Mayalibit Bay, Raja Ampat, Indonesia - Dian Oktaviani; Setiya Triharyuni; Duto Nugroho (Biodiversitas Journal of Biological Diversity, 2019)
Abstract: Oktaviani D, Triharyuni S, Nugroho D. Population parameters and bio-exploitation status of Indian mackerel (Rastrelliger kanagurta Cuvier, 1816) in Mayalibit Bay, Raja Ampat, Indonesia. Biodiversitas 20: 3545-3552. A small-scale fishery in Mayalibit bay, Raja Ampat is one among rare fisheries systems existing in Indonesia. The area already designated as a conservation zone, and Indian mackerel is the main target species by fishers. This species plays a significant role in supplying domestic food. Fisher harvest with a small wooden boat, no engine, one-night fishing using Petro-lamp, and harvested with a scoop net. Monthly based biological observations on population parameters were carried out from March 2011 to April 2012. The result shows that the fish landed with size from 10.0 to 27.0 cm, and 70% of the sample is within 21-23 cm length. Monthly length-weight relationships indicate b value statistically equal to 3. The average unsexed Fulton condition factor index is 1.516 + 0.13 and illustrates the fishes were in suitable environmental conditions. The growth rate (K) is estimated at 0.97, while length infinity (L?) is 28.4 cm. To evaluate the fishery, repeated observation of fishing in Mayalibit bay conducted in 2016. A productivity and susceptibility analysis was applied to predict its bio-exploitation status, and the results indicate that harvest levels are relatively at low-to-medium risk. Nevertheless, most of the fish caught in the bay by traditional knowledge consisted of mature cohorts while limited desk study to semi-industrial fishing targetted the same species in surrounding waters indicated that a significant proportion of undersize or immature individuals are in their landing. This phenomenon suggested that managing the existing local knowledge could significantly contribute to maintaining sustainable spawning stocks in the conservation zone.